Demographic and socio-psychological determinants of high-level migration from the Philippines to the United States - Jayme, Josefina B. (Philippine Journal of Psychology, 1974)
Studied the demographic and sociopsychological factors underlying high-level migration from the Philippines to the US by means of responses to a questionnaire completed by 319 of the 510 Filipino graduate students in the US who were sampled. Three variables emerged as the best predictors of migration intentions: (a) anchorage, or the number and nature of ties binding a person to his homeland; (b) perception of comparative opportunities, or a person's valuation of relative social, economic, and professional opportunities in the Philippines and in the US; and (c) source of support for US study. These 3 variables proved in addition to be useful intervening variables, accounting for 16 of the 22 other significant correlations with migration intentions. "Push" factors from the Philippines were found to be more relevant to migration than "pull" factors from the US: Valuation of the Philippines was consistently a better predictor of migration than nature of experience in or attitudes toward the US. Respondents tended to evaluate the Philippines less favorably than the US; they also tended to identify more with the US than the Philippines. These findings apparently put the responsibility and capacity for curbing skilled migration on the Philippines.